Analisis Daya Dukung Lahan untuk Permukiman di Kota Bukittinggi - Mahkota, Indra; Febriandi, Febriandi (Lembaga Yasin AlSys, 2024)
Bukittinggi City, with the land conversion to built-up land continues to increase and the availability of land that does not increase, faces difficulties in utilizing land for settlements along with increasing population growth. The purpose of this study is to analyze the suitability of land for settlements and the carrying capacity of Bukittinggi City's residential land for the next 30 years. The quantitative descriptive research method with data presented through tables and maps, calculations refer to the Ministry of Environment's 2014 carrying capacity guidelines and RP3KP. The results of the study indicate that the area of land suitable for settlements is Suitable (S2) covering 710 ha, less suitable (S3) covering 1,147 ha, and not suitable covering 430 ha. For the carrying capacity of Bukittinggi City settlements, in Guguk Panjang District it is in the deficit class, with a DDPm value of 0.24, while 2 other districts are in the surplus class, with Mandiangin Koto Selayan District valued at 2.42, and Aur Birugo Tigobaleh District of 4.09. And for a period of 30 years, 2032, 2042, and 2052, Mandiangin Koto Selayan sub-district and Aur Birugo Tigobaleh sub district still have a surplus while Guguk Panjang sub-district is still in deficit.